Link-time static analysis for efficient separate compilation of object-oriented languages. - Privat, Jean (Software engineering notes.)
Compilers used in industry are mainly based on a separate compilation framework. However, the knowledge of the whole program improves efficiency of object-oriented language compilers, therefore more efficient implementation techniques are based on a global compilation framework.In this paper, we propose a compromise by including three global compilation techniques (type analysis, coloring and binary tree dispatching) in a separate compilation framework. Files are independently compiled into standard binary files with unresolved symbols. The program is build by linking object files: files are gathered and analyzed, some link code is generated then symbols are resolved.